Spinal Deformity in Sotos Syndrome: First Results of Growth-friendly Spine Surgery. Issue 9 (October 2020) - Verhofste, Bram P.; Glotzbecker, Michael P.; Marks, David S.; Birch, Craig M.; McClung, Anna M.; Emans, John B.
Abstract : Background: Sotos syndrome (SS), or cerebral gigantism, describes children with macrocephaly, craniofacial abnormalities, general overgrowth, ligamentous laxity, developmental delay, and neurological disabilities. Fewer than 500 cases have been reported since Sotos and colleagues described the condition in 1964 and no literature exists on the management of spinal deformity in children under 10 years old. The aims of this study were: (1) to characterize the presentation of spinal deformities in patients with SS; and (2) to provide preliminary results of growth-friendly instrumentation (GFI) in these children. Methods: Thirteen children (9 boys) with SS and minimum of 2-year follow-up were identified from 2 multicenter early-onset scoliosis (EOS) databases (1997-2017). Mean age at index surgery and follow-up duration were 5.0 years (range, 1.8 to 10 y) and 7.2 years (range, 2.1 to 14.9 y), respectively. Patients underwent GFI for a mean of 5.7 years (range, 2 to 10.2 y), with an average of 9 lengthenings (range, 2 to 18). Definitive spinal fusion was performed in 4 patients (31%). Major curve magnitude, T1-T12 and T1-S1 lengths, thoracic kyphosis, and lumbar lordosis were evaluated preindex, postindex, latest GFI, and postfusion, when possible. Results: Five thoracolumbar (38%), 4 double major (31%), 2 main thoracic (15%), and 2 double thoracic curves (15%) were seen that spanned a mean of 6.8 levels (5 to 9). Major curves improved 36% (range, 5% to 71%), from a mean of 71 degrees (range, 48 to 90 degrees) to 46 degrees (range, 20 to 73 degrees) postindex surgery ( P <0.001). Major curves remained stable at a mean of 52 degrees (range, 20 to 87 degrees) at latest GFI ( P =0.36). True T1-T12 and T1-S1 growth velocities during GFI were 0.5 mm/mo (range, 0.4 to 0.8 mm/mo) and 0.8 mm/mo (range, 0.1 to 2.1 mm/mo), respectively. Twenty-six complications occurred in 9 patients (69%) averaging 2 complications per patient (range, 0 to 7). Conclusions: This is the first study to evaluate the outcomes of GFI in children with SS and EOS. Compared with published data for outcomes of GFI in EOS, children with SS may have less major curve correction. Growth-friendly surgery remains an effective treatment method for EOS in patients with SS. Levels of Evidence: Level IV—retrospective case-series.